Structural and Phylogenetic Profiles of Muscle Actins from Cephalopods - Y. Ochiai; S. Watabe; G. Wang (Journal of Basic & Applied Sciences, 2021)
Structural properties of cephalopod muscle actins have not been characterized in detail to date. Sequences of these actins have been determined by cDNA cloning from the arm muscles of four cephalopod species, namely, Japanese common squid Todarodes pacificus, spear squid Loligo bleekeri, common cuttlefish Sepia esculenta, and common octopus Octopus vulgaris. The sequence identities of the deduced amino acid sequences among the cephalopod actins were around 98%, and the substitutions were mostly limited to Subdomains 1 and 3. Phylogenetic analyses revealed that cephalopod actins formed one cluster and were distinguishable from the bivalve counterparts. The modeled tertiary structure of squid actin was very similar to that of rabbit counterpart, but the structures of Subdomains 1 and 3 were slightly different.